Letter: now is the time to remove complexity from HCV guidelines to ensure that elimination remains a priority. Issue 6 (28th August 2020) - Turnes, Juan; Hezode, Christophe; Hernandez, Candido; Mangia, Alessandra
Abstract : LINKED CONTENT This article is linked to Singh et al and Singh and Shalimar papers. To view these articles, visit https://doi.org/10.1111/apt.15633 and https://doi.org/10.1111/apt.16011